Main direction of optimization of agrotechnics of growing seedlings of woody plants with closed root system in Mangistau desert - Belozerov, I.F.; Tolep, N.A.; Umirbayeva, F.U.; Nazarova, A.A.; Bergenkulova, S.Zh. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2024)
The objective of this study is to optimize the agricultural technology of growing seedlings of woody plants with a closed root system in the arid conditions of Mangistau by conducting field experiments. Based on the dispersion and correlation analysis of the collected research material, it was concluded that the following agricultural practices are the most preferable in terms of biometric and physiological indicators of growth and development of woody plants: 1) Maintaining the pre-irrigation level of soil moisture within 70‒80 % of the full field moisture capacity, 2) Mixing plant and peat soil in a ratio of 1: 1 and 3) Monthly fertilizing with mineral complex fertilizer at the rate of 75 g / m2. The most effective covering materials in the conditions of the Mangistau desert for preventing moisture evaporation under green spaces are such covering materials as Zeba super sorbent, sludge from treatment facilities and medium and fine gravel. The results of the research were successfully tested during mass propagation of 107 species, forms and varieties of the most promising introduced plants from 32 genera and 17 families (65,340 containers in total).
Ауылшаруашылығын өсіру технологиясын оңтайландырудың негізгі бағыттары жабық тамыр жүйесі бар ағаш өсімдіктерінің көшеттері Маңғыстау шөлінің құрғақ жағдайында
Основные направления оптимизации агротехники выращивания саженцев древесных растений с закрытой корневой системой в аридных условиях пустыни Мангистау
Keywords: optimization; agricultural technology; woody plants; seedlings; containers; field experiment; survival rate; growth